Pengaruh Manajerial Kepala Sekolah dan Kompetensi Guru Terhadap Peningkatan Mutu Sekolah Dasar di Gugus I Kecamatan Gunung Talang: Penelitian - Anggraini, Desi; Fazis, Muhammad; David, David (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The main problem in this thesis is the decline in school quality due to the low managerial skills of school principals and the competency of elementary school teachers in Cluster I, Gunung Talang District, which is seen from the ANBK results. This study uses a correlational method with a quantitative approach and involves 122 school principals and teachers as the population. Each questionnaire item is tested for validity and reliability with a significance level of 0.05. The results show that the managerial skills of school principals have a significant effect on improving the quality of education (t count 6.823 > t table 1.985), and teacher competency also has a significant effect (t count 6.338 > t table 1.985). Simultaneously, both variables have a significant effect on improving school quality with a significance value of 0.000 < 0.05 and F count 31.385 > F table 3.946. Thus, the study concludes that: (1) the principal's managerial skills, (2) teacher competencies, and (3) both together have a positive and significant influence on improving the quality of Elementary Schools in Cluster I, Gunung Talang District.